2017
DOI: 10.3390/met7120535
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of an Overheated Aluminum Droplet Wetting a Zinc-Coated Steel Surface

Abstract: Wetting steel surfaces with liquid aluminum without the use of flux can be enabled by the presence of a zinc-coating. The mechanisms behind this effect are not yet fully understood. Research results on single aluminum droplets falling on commercial galvanized steel substrates revealed the good wetting capability of zinc coatings independently from the coating type. The final wetting angle and length are apparently linked to the time where zinc is liquefied during its contact with the overheated aluminum melt. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…Similar results were also expected based on numerical simulation [14]. Computational fluid dynamics (CFD) simulation results showed that molten zinc was laterally pushed as the molten metal propagated to the side.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar results were also expected based on numerical simulation [14]. Computational fluid dynamics (CFD) simulation results showed that molten zinc was laterally pushed as the molten metal propagated to the side.…”
Section: Introductionsupporting
confidence: 84%
“…Fig. 3 Comparison of the experimental (according to [14]) and simulation results (workpiece thickness: 0.8 mm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second article in this issue, Gatzen et al [2] utilized both experimental and numerical techniques to investigate the wetting process of an aluminum droplet on a zinc-coated steel surface. The final wetting angle and length were linked to the time where zinc was liquefied during its contact with the overheated aluminum melt, leading to the assumption that the interaction was basically a fluid dynamic effect of liquid aluminum getting locally alloyed by zinc.…”
Section: Contributionsmentioning
confidence: 99%
“…The final wetting angle and length were linked to the time where zinc was liquefied during its contact with the overheated aluminum melt, leading to the assumption that the interaction was basically a fluid dynamic effect of liquid aluminum getting locally alloyed by zinc. To further investigate this process, Gatzen et al [2] developed a numerical model to describe the transient behavior of droplet movement and mixing with the liquefied zinc layer to understand the spreading dynamics. Their simulations revealed a displacement of the molten zinc after the impact of the droplet, which ultimately led to an accumulation of zinc in the outer weld toe after solidification.…”
Section: Contributionsmentioning
confidence: 99%